Making Hard Choices: Using Data to Make Collections Decisions - Edwards, Susan Elizabeth (Qualitative and Quantitative Methods in Libraries; Vol 4 No 1 (2015): March 2015 Issue, 2017)
Research libraries spend millions of dollars acquiring, storing and accessing collections -- but how well do the collections we build meet the needs of our users? How do we know if we are equitably supporting a wide array of disciplines on campus, and more importantly, how well we support the research mission of our institution? In order to arrive at meaningful answers to these questions, we need to go beyond simple size measures such as dollars spent, volumes added, and number of e-journals licensed; and even beyond usage metrics such as interlibrary loan, total circulation and e-usage statistics. This paper will outline several approaches being used at Berkeley, including a citation analysis of doctoral dissertations, and how this new data is helping guide these difficult decisions.